Actors and modes of governance of cities in Africa - (:unkn) unknown (My University, 2022)
Africa is characterized by strong urbanization and is accompanied by multiple challenges in terms of urban governance by different actors according to the political contexts on the continent. Thus, this article, essentially based on a theoretical study, aims to better understand the main actors and methods of urban management in Africa. This investigation
Keywords: African Research